Dentin pretreatment and adhesive temperature as affecting factors on bond strength of a universal adhesive system - Sutil, Bruna Gabrielle da Silva; Susin, Alexandre Henrique (Journal of Applied Oral Science, 2017)
Objectives: To evaluate the effects of dentin pretreatment and temperature on the bond strength of a universal adhesive system to dentin. Material and Methods: Ninety-six extracted non-carious human third molars were randomly divided into 12 groups (n=8) according to Scotchbond Universal Adhesive (SbU) applied in self-etch (SE) and etch-and-rinse (ER) mode, adhesive temperature (20°C or 37°C) and sodium bicarbonate or aluminum oxide air abrasion. After composite build up, bonded sticks with cross-sectional area of 1 mm2 were obtained to evaluate the microtensile bond strength (μTBS). The specimens were tested at a crosshead speed of 0.5 mm/min on a testing machine until failure. Fractured specimens were analyzed under stereomicroscope to determine the failure patterns in adhesive, cohesive (dentin or resin) and mixed fractures. The microtensile bond strength data was analyzed using two-way ANOVA and Tukey's test (α=5%). Results: Interaction between treatment and temperature was statistically significant for SbU applied in self-etch technique. Both dentin treatments showed higher bond strength for ER mode, regardless of adhesive temperature. When compared to control group, sodium bicarbonate increased bond strength of SbU in SE technique. Adhesive temperature did not significantly affect the μTBS of tested groups. Predominantly, adhesive failure was observed for all groups. Conclusions: Dentin surface treatment with sodium bicarbonate air abrasion improves bond strength of SbU, irrespective of adhesive application mode, which makes this approach an alternative to increase adhesive performance of Scotchbond Universal Adhesive to dentin.